Collaborative Governance dalam Pengelolaan Badan Usaha Milik Desa (Bumdes) “Cipta Karya Unggul” di Desa Tipar Kidul Kecamatan Ajibarang Kabupaten Banyumas - Kurniawan, Defri; Amartha, Putri; Azizah, Hidayatul; Fauziah, Mitha (Indonesian Journal Publisher, 2025)
Village-Owned Enterprises (BUMDes) play an essential role in improving rural economic development through the management of local potential. This study aims to identify the process of Collaborative Governance in the management of BUMDes “Cipta Karya Unggul” in Tipar Kidul Village, Ajibarang District, Banyumas Regency. This research uses a descriptive qualitative approach with data collected through interviews, observation, and documentation, while informants were selected using purposive sampling. The findings indicate that the management of BUMDes Cipta Karya Unggul involves collaboration among the village government, the community, and the private sector, particularly PT. Sinar Tambang Artha Lestari (PT STAR). This collaboration reflects the principles of Collaborative Governance—participatory, transparent, and goal-oriented— resulting in increased village income and community welfare. The success of this collaboration is supported by facilitative leadership, open communication, and mutual trust among stakeholders. Therefore, the application of the Collaborative Governance model is an effective strategy for strengthening sustainable village economic governance.